EVOLUÇÃO POPULACIONAL DE PLANTAS ESPONTÂNEAS EM SISTEMAS DE PRODUÇÃO ORGÂNICA DE SOJA - Carbonera, Roberto; Lüdtke, Aleisson; Wunsch, Jaime A.; Quadros, Valmir J. d. (Salão do Conhecimento, 2013)
Resumo